Jungle passports : fences, mobility, and citizenship at the Northeast India-Bangladesh border - Sur, Malini (Ethnography of political violence., 2021)
In Jungle Passports Malini Sur follows the struggles of the inhabitants of what are now the borderlands of Northeast India and Bangladesh and their efforts to secure shifting land, gain access to rice harvests, and smuggle the cattle and garments upon which their livelihoods depend.